Pleistocene climate fluctuations as the major driver of genetic diversity and distribution patterns of the Caspian green lizard, Lacerta strigata Eichwald, 1831. Issue 11 (2nd May 2021) - Saberi‐Pirooz, Reihaneh; Rajabi‐Maham, Hassan; Ahmadzadeh, Faraham; Kiabi, Bahram H.; Javidkar, Mohammad; Carretero, Miguel A.
Abstract: Green lizards of the genus Lacerta have served as excellent models for studying the impact of Pleistocene climatic oscillations on genetic structures. The Caspian green lizard, Lacerta strigata, occupies various habitats across the Caucasus and the South Caspian Sea, with the Hyrcanian Forests and north of the Alborz Mountains forming the core of the range. This study aimed to re‐examine the phylogenetic relationships of L. strigata with other congeneric members and to assess the genetic structure and historical demography of the species. Furthermore, Species Distribution Models (SDMs) were performed to infer the species' potential habitat suitability and were then projected on climate scenarios reflecting current and past (6 ky and 21 ky before present) conditions. A total of 39 individuals collected from most of the distribution range, together with additional lacertid species sequences from the GenBank database, were examined using mtDNA (Cyt b and 12S ribosomal RNA) and nuclear (C‐mos and β‐fibrinogen) sequence data. Based on the phylogenetic analyses, L. strigata was found to be a sister taxon to all other members of the genus. The species included two main clades (regional western and eastern) that diverged in a period between the Early and Middle Pleistocene. Based on the BBM and S‐Diva analyses, both dispersal and vicariance events explained the phylogeographic structure of the species in the Hyrcanian Forests. The historical demographic analyses using Bayesian skyline plots showed a mild increase in the effective population size from about 120 Kya for the western regional clade. According to phylogeographic structures and SDMs evidence, as in other species within the region, it appears that the south of the Caspian Sea (Hyrcanian Forests), and the Alborz Mountains acted as multiple refugia during cold periods and promoted expansion outwards amid the warm periods. Overall, the results provided evidence that the genetic structure of the species has been influenced by the Pleistocene climatic fluctuations. Abstract : The Caspian green lizard, Lacerta strigata, occupies various habitats across the Caucasus and the South Caspian Sea, with the Hyrcanian Forests and north of the Alborz Mountains forming the core of the range. The regions acted as multiple refugia during cold periods and promoted expansion outwards amid the warm periods. Overall, the results provided evidence that the genetic structure of the species has been influenced by the Pleistocene climatic fluctuations.